Законодавчі основи українського транскордонного співробітництва - Бурдяк, В. І.; Burdiak, V.I. (Східноєвропейський національний університет імені Лесі Українки, 2013)
The author notes that in the past decade, Ukraine adopted a number of important legal documents aimed at strengthening its cross-border cooperation with neighboring countries-members and non-members of the European Union. The documents allow for a more practical needs of cross-border cooperation, but also contain a number of provisions that require further development and changes, especially under the influence of globalization processes in the world, the EU enlargement, changes in international politics. Operating in Ukraine legislative framework for cross-border cooperation should be further improved.
Ukrainian legislative framework of cross-border cooperation
В.І.Бурдяк, д. політ.н., проф. кафедри політології та державного управління Чернівецького національного університету імені Юрія Федьковича (Україна, м. Чернівці)
Keywords: cross-border cooperation; the legislative framework; Ukraine; the EU